2015
DOI: 10.1128/mcb.00742-15
|View full text |Cite
|
Sign up to set email alerts
|

NSun2 Promotes Cell Growth via Elevating Cyclin-Dependent Kinase 1 Translation

Abstract: cThe tRNA methytransferase NSun2 promotes cell proliferation, but the molecular mechanism has not been elucidated. Here, we report that NSun2 regulates cyclin-dependent kinase 1 (CDK1) expression in a cell cycle-dependent manner. Knockdown of NSun2 decreased the CDK1 protein level, while overexpression of NSun2 elevated it without altering CDK1 mRNA levels. Further studies revealed that NSun2 methylated CDK1 mRNA in vitro and in cells and that methylation by NSun2 enhanced CDK1 translation. Importantly, NSun2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 43 publications
(57 reference statements)
4
90
0
2
Order By: Relevance
“…In agreement with the findings in Fig. 1B and in previous studies [28], neither overexpression of NSun2 nor knockdown of NSun2 altered the levels of p27 and CDK1 mRNAs in a measurable manner (Fig. 5B).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with the findings in Fig. 1B and in previous studies [28], neither overexpression of NSun2 nor knockdown of NSun2 altered the levels of p27 and CDK1 mRNAs in a measurable manner (Fig. 5B).…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that the regulation of p27 by NSun2 may not involve altered p27 mRNA transcription or turnover. Because NSun2 had been shown to regulate the expression of p53, p16, E2F3, Bak1, ErbB2, and CDK1 by methylating the mRNAs encoding these proteins [2628], we tested if NSun2 was capable of methylating p27 mRNA. To this end, the p27 mRNA fragments described in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of the m 5 C writer NOP2/Sun RNA methyltransferase family member 2 (NSUN2) is tightly regulated during the cell cycle and its overexpression delays replicative senescence through methylation of Cyclin-dependent kinase 1 (CDK1) and the CDK inhibitor 1B (p27 KIP1 ) transcripts. Deposition of m 5 C in the CDK1 3′UTR enhances its translation, while m 5 C in the 5′UTR of p27 KIP1 represses its translation, resulting in increased cellular proliferation 56, 57 . Deposition of hm 5 C by methylcytosine dioxygenases 58 in mRNA correlates with higher association with polyribosomes in Drosophila melanogaster 59 .…”
Section: Rna Modification: the Epitranscriptomementioning
confidence: 99%